THE INTERNALITY OF EVALUATION TO IMPROVE EFL PERFORMANCE OF COURSES ON GRAMMAR (Jurnal Bahasa Lingua Scientia, 2014)
This paper reports qualitative program evaluation research and its implication. The site of the research is a study program in English which had undergone changes in its student. Based on theory and purposive sampling, the case being investigated was one out of ten classes of the grammar course, based on its heterogeneity in the GPA of the students, and based on the consideration that the instructor of the class  being the designer of the course. The focus of the evaluation was on the content, the student performance and classroom interaction. The researcher, historically part of the site, was the main instrument in data collection through participant and non-participant observation, serving the role as an insider in the research evaluation. Classroom events were observed and video recorded. Students and instructors of the grammar course were interviewed, and documents were collected and scrutinized. The result of the research was disseminated. Mechanism has been developed in on-going evaluation of the course through staff development program, and through learning organization.
Keywords: evaluation; student performance; classroom interaction; grammar course